The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1089/neu.2016.4885
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Intervention Compared to Telephone Counseling Early after Mild Traumatic Brain Injury: A Randomized Trial

Abstract: Many patients do not return to work (RTW) after mild traumatic brain injury (mTBI) because of persistent complaints that are often resistant to therapy in the chronic phase. Recent studies suggest that psychological interventions should be implemented early post-injury to prevent patients from developing chronic complaints. This study is a randomized, controlled trial that examines the effectiveness of a newly developed cognitive behavioral therapy (CBT) intervention (CBTi) compared to telephonic counseling (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
54
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 44 publications
4
54
1
Order By: Relevance
“…From the 7 studies meeting the inclusion criteria, there was a total of 1108 adult participants of which 68.8% (n = 763) were male. The participants ranged from 18 to 80 years of age and were mostly from the United States (n = 919), Denmark (n = 155), the Netherlands (n = 91), and England (n = 46) . Of the 7 studies, 3 studies focused on military staff and 4 focused on nonmilitary persons .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From the 7 studies meeting the inclusion criteria, there was a total of 1108 adult participants of which 68.8% (n = 763) were male. The participants ranged from 18 to 80 years of age and were mostly from the United States (n = 919), Denmark (n = 155), the Netherlands (n = 91), and England (n = 46) . Of the 7 studies, 3 studies focused on military staff and 4 focused on nonmilitary persons .…”
Section: Resultsmentioning
confidence: 99%
“…The participants ranged from 18 to 80 years of age and were mostly from the United States (n = 919), Denmark (n = 155), the Netherlands (n = 91), and England (n = 46) . Of the 7 studies, 3 studies focused on military staff and 4 focused on nonmilitary persons . Of the studies that focused on military staff, 2 studies enrolled active duty or active reserve/guard duty service members with confirmed or suspected mTBI and one study focused on veteran military staff.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations